The Issues Faced by Teachers in IPAS Learning under the Merdeka Curriculum in Grade IV of SD Negeri 16 Kinali - Yesi Rasnita Sari; Ayunis Ayunis; Stavinibelia Stavinibelia; Yona Syaida Oktira (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The background of this research is based on the Independent Learning Curriculum that has been implemented at SD Negeri 16 Kinali which is inseparable from various existing problems, both in terms of planning, implementation, and assessment. In this study, teachers experienced limited teaching materials, teachers had difficulty practicing in science learning, and teachers experienced difficulties in conducting assessments. Therefore, this study aims to: Determine the Problems experienced by Teachers in implementing the Independent Learning Curriculum in science learning in grade IV of SD Negeri 16 Kinali. This study uses a qualitative approach with a descriptive research type. The research subjects were the principal and class teachers. Data collection was carried out through observation, interviews and documentation. The data analysis techniques carried out were data reduction, data presentation, and drawing conclusions. While the validity of the data was tested using Triangulation Techniques. Based on the research results obtained, class teachers in Science Learning need to prepare Planning, Implementation, and assessment in learning. Teachers need to identify learning objectives, analyze student needs, select learning materials and methods, prepare teaching materials, plan learning activities, compile learning media and communicate expectations to students.